Treatment Strategy after Incomplete Endoscopic Resection of Early Gastric Cancer - Kim, Sang Gyun (Clin Endosc, 2016)
Endoscopic resection of early gastric cancer is defined as incomplete when tumor cells are found at the resection margin upon histopathological examination. However, a tumor-positive resection margin does not always indicate residual tumor; it can also be caused by tissue contraction during fixation, by the cautery effect during endoscopic resection, or by incorrect histopathological mapping. Cases of highly suspicious residual tumor require additional endoscopic or surgical resection. For inoperable patients, argon plasma coagulation can be used as an alternative endoscopic treatment. Immediately after the incomplete resection or residual tumor has been confirmed by the pathologist, clinicians should also decide upon any additional treatment to be carried out during the follow-up period.